2002
DOI: 10.1016/s0896-6273(02)00770-5
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-Associated Glycoprotein Interacts with the Nogo66 Receptor to Inhibit Neurite Outgrowth

Abstract: Myelin inhibitors of axonal regeneration, like Nogo and MAG, block regrowth after injury to the adult CNS. While a GPI-linked receptor for Nogo (NgR) has been identified, MAG's receptor is unknown. We show that MAG inhibits regeneration by interaction with NgR. Binding of and inhibition by MAG are lost if neuronal GPI-linked proteins are cleaved. Binding of MAG to NgR-expressing cells is GPI dependent and sialic acid independent. Conversely, NgR binds to MAG-expressing cells. MAG, but not a truncated MAG that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
377
6
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 542 publications
(395 citation statements)
references
References 48 publications
8
377
6
4
Order By: Relevance
“…They conclude, therefore, that Nogo-66 is the main inhibitor, because when only Nogo-66 is blocked does considerable regeneration occur. By contrast, we showed that Mag could compete with Nogo-66 for binding to Ngr 36 .…”
Section: Pertussis Toxincontrasting
confidence: 59%
See 2 more Smart Citations
“…They conclude, therefore, that Nogo-66 is the main inhibitor, because when only Nogo-66 is blocked does considerable regeneration occur. By contrast, we showed that Mag could compete with Nogo-66 for binding to Ngr 36 .…”
Section: Pertussis Toxincontrasting
confidence: 59%
“…library, and they found a new ligand that was shown to be Mag 35 . At the same time, our group had co-precipitated the two proteins and had also identified Ngr as a receptor for Mag 36 . Together, these two studies provided compelling evidence that Ngr is required for Mag to exert its inhibition.…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 94%
See 1 more Smart Citation
“…Nogo-66, together with both MAG and OMgp, bind and activate the same receptor, the neuronal, glycosyl-phosphatidyl-inositol (GPI)-anchored Nogo-66 Receptor (NgR; Fournier et al, 2001;Domeniconi et al, 2002;Liu et al, 2002a;Wang et al, 2002a) with additional molecules including p75 NTR , Lingo-1 and TAJ/TROY required for signaling (Mi et al, 2004;Shao et al, 2005;Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50] As an apparent point of convergence in inhibitory signaling, NgR has taken the stage as a target of strategies aimed at increasing plasticity in the injured spinal cord. A competitive antagonist of NgR, NEP1-40, blocks the inhibitory action of myelin in vitro 51 and enhances both growth of supraspinal axons and functional recovery when administered intrathecally or systemically after thoracic hemisection.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 99%